Structure–Activity Mechanism of Sodium Ion Adsorption and Release Behaviors in Biochar - Kai Yang; Wei Jing; Jing Wang; Kaizhao Zhang; Yaoming Li; Meng Xia; Kun Zhang; Jiefei Mao (Agriculture, 2024)
Biochar is a soil amendment that has the potential to effectively improve soil salinization. However, there is a paucity of studies on sodium adsorption using biochar, and the adsorption mechanism remains unclear. To better understand the adsorption mechanism of Na+ on the surface of biochar, both pyrochar and hydrochar were produced at different temperatures. The capacity and influencing factors of Na+ adsorption in biochar were analyzed via batch adsorption experiments. Pore filling dominated the Na+ adsorption in the concentration of the NaCl solution when it was ≤100 mg/L, where wheat straw pyrochar (WB, 3.95–4.94 mg/g Na) and poplar wood chip pyrochar (PB, 0.62–0.70 mg/g Na) presented the release and adsorption of Na+, respectively. When the concentration of the NaCl solution was >100 mg/L, the adsorption capacity of WB (25.44–36.45 mg/g) was significantly higher than PB (4.46–6.23 mg/g). Both the adsorption and release of Na+ in hydrochar was insufficient. In a high concentration of NaCl solution, ion exchange became the key mechanism determining the adsorption of Na+ in pyrochar, in which K+ contributed to more than 94% of the Na+ adsorption. The findings proposed strategies for the structural design of biochar used for Na adsorption. These will promote the utilization of solid biowaste for sodium adsorption and the potential of soil salinization amendment for agriculture in arid lands.